Effectiveness of Health Services through the JKN Mobile Application at the BPJS Kesehatan Palu Branch in Palu City - Ashari, Muhammad Rizki; Lawero, Fadila Angraini; Patui, Nurhaya S; Sulaiman, Miftahul Haerati (Tadulako University, 2025)
Mobile JKN is an application launched or issued by BPJS Health which aims to make it easier for the BPJS Health participant community to obtain services and all JKN-KIS membership information. The city of Palu itself still has minimal JKN mobile application users. This research aims to determine the effectiveness of health services based on the JKN mobile application at BPJS Health Palu Branch in Palu City. The method used in this research is qualitative with a case study approach. Data collection techniques were carried out using in-depth interviews, observation, source triangulation and technical triangulation. The results obtained are that the effectiveness of health services based on the JKN mobile application is very good, human resources are adequate, the concept of paying contributions is practical, the number and quality of services produced is increasing, accessing the application without time limits but at certain times there are still problems with slow login, and Practical and easy service procedures. It is hoped that BPJS Health Palu Branch can pay attention to the work performance of the Mobile JKN application, especially when accessing the application.